Optimal Restoration/Maintenance Switching Sequence of Unbalanced Three-Phase Distribution Systems - Lopez, Juan Camilo; Franco, John F. [UNESP]; Rider, Marcos J.; Romero, Ruben [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2018)
This paper presents a mixed-integer non-linear programming (MINLP) model for the optimal restoration/maintenance switching sequence of unbalanced three-phase electrical distribution systems. Once the protection coordination has identified and cleared a faulty zone, the proposed MINLP model determines the status of remotely controlled switches and the dispatchable distributed generation (DG) units, used to deenergized the troubled section of the network and supply as much load as possible. The restoration considers the switching sequence over a discrete horizon, guaranteeing that the operational constraints of the distribution system are not violated Functions in every step of the sequence. Furthermore, a set of linearization strategies are presented to transform the proposed MINLP, model into a mixed-integer linear programming (MILP) model. The use of MILP models guarantees convergence to optimality by applying convex optimization techniques. Tests are performed on an unbalanced three-phase radial distribution system consisting of 123 nodes, 12 switches, and three dispatchable DG units. The obtained results show that the proposed optimization model is a holistic procedure that can be used to efficiently manage power restoration or to minimize isolated areas in case of scheduled maintenance in modern electrical distribution systems.
Keywords: Mixed integer linear programming; restoration/maintenance switching sequence; unbalanced three-phase electrical distribution systems